2011
DOI: 10.1093/eurheartj/ehr297
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic postconditioning revisited: lack of effects on infarct size following primary percutaneous coronary intervention

Abstract: This randomized study suggests that p-cond during primary PCI does not reduce infarct size or improve myocardial function recovery at both short- and long-term follow-up and might have a potential harmful effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
201
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(210 citation statements)
references
References 31 publications
6
201
3
Order By: Relevance
“…In 2013 a single‐center study by Freixa et al showed rather a significant deterioration in the myocardial salvage and the myocardial salvage index along with reduced pump function 6 months after myocardial ischemia 9. These results correspond to data published by Hahn et al from a multicenter study of 700 patients (POST [Effects of Postconditioning On Myocardial Reperfusion] trial, https://clinicaltrials.gov/show/NCT00942500) that was conducted between 2009 and 2012, also showing no cardiprotective effect 10.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013 a single‐center study by Freixa et al showed rather a significant deterioration in the myocardial salvage and the myocardial salvage index along with reduced pump function 6 months after myocardial ischemia 9. These results correspond to data published by Hahn et al from a multicenter study of 700 patients (POST [Effects of Postconditioning On Myocardial Reperfusion] trial, https://clinicaltrials.gov/show/NCT00942500) that was conducted between 2009 and 2012, also showing no cardiprotective effect 10.…”
Section: Introductionmentioning
confidence: 99%
“…Further, patients with larger infarcts or those with an anterior MI are more likely to benefit from such an intervention. 5,6,27,32 Indeed, in our initial study, there was a trend toward a stronger effect of sevoflurane in patients with an anterior MI on assessing myocardial injury by release of cardiac enzymes. 20 In the current study, we did not observe an overall clinically meaningful effect of sevoflurane on the long-term assessment of LV function, myocardial scarring, or hibernating myocardium.…”
Section: Discussionmentioning
confidence: 79%
“…4,5 However, other recent studies, including a study published by our group, did not show clinical benefit from ischemic conditioning, suggesting that the precise mode of applying ischemic conditioning should be explored further. 6,7 In particular, it seems that it is important to apply the ischemic conditioning intervention as early as possible. Administration of a pharmacological agent that mimics ischemic conditioning can be initiated early and may be suitable for all patients with STEMI receiving reperfusion therapy, including fibrinolysis and pPCI.…”
Section: Résumémentioning
confidence: 99%
“…Clinical trials reported conflicting results of POC application during the percutaneous coronary intervention of the infarct related artery. POC triggered cardioprotection [8] or did not protect myocardium against I/R injury at all [18]. Such observed discrepancies may be related to diverse scenarios of coronary artery occlusion.…”
Section: Discussionmentioning
confidence: 96%